IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI DAN MANAJEMEN PERTANAHAN NASIONAL (SIMTANAS) PADA KANTOR PERTANAHAN KABUPATEN BANTAENG - Barani, Ishaq Bambang; Madani, Muhlis; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine and provide an overview of how the implementation of the National Land Management Information and Management System (SIMTANAS) policy in the land office of Bantaeng Regency. The number of informants in this study were 8 people, including the community. This study uses a qualitative approach. This study describes and correctly interprets the nature and state of the situation and condition of the symptoms and their development by using the methods of observation, interviews, and documentation. The results of this study indicate that the interpretation and description of the implementation of the National Land Information and Management System Policy (SIMTANAS) at the Bantaeng Regency Land Office indicates that the National Land Information and Management System Policy (SIMTANAS) has been implemented in accordance with existing provisions although there are things that need to be done. Made and there is a hope. These considerations are land administration issues that need improvement both in terms of facilities and infrastructure as well as human resources.